THE INFLUENCE OF LOCAL FOOD SATISFACTION AND DESTINATION IMAGE ON OVERALL TOURIST EXPERIENCE THROUGH TOURIST PERCEPTION - Buana, Salsabila Ayunda Martsa; Tunjungsari, Hetty Karunia (Graduate Program of Universitas Tarumanagara, 2025)
This study comprehensively investigates the multifaceted influence of Local Food Satisfaction and Destination Image on the Overall Tourist Experience, with a particular focus on analyzing the mediating role of Tourist Perception. In today's tourism environment, where genuine experiences and favorable impressions are essential to traveler choices and contentment, a deep comprehension of these influencing elements is vital for achieving success in the destination. Using a quantitative method, this study gathered data from 200 participants who possessed previous tourism experiences, via the dissemination of a structured questionnaire. Data examination was performed via Structural Equation Modeling (SEM) to empirically evaluate the proposed direct and indirect connections between the variables in the conceptual framework. The results clearly demonstrate that both Local food satisfaction and a favorable destination image have a strong and significant impact on tourists’ views of a location. Additionally, our findings affirm that Tourist Perception serves as an essential partial mediator, successfully conveying the beneficial impact of local food gratification and destination perception towards an improved complete tourist experience. The real-world applications of this study offer significant direction for destination coordinators, travel promoters, and various participants in formulating enhanced approaches to improve the visitor experience, by highlighting the enhancement of exceptional local food options and the strengthening of a genuine and favorable destination image